Inculcating universal values via English language education - Mohideen, Haja (2017)
The teaching and learning of languages need not necessarily be focused entirely on the acquisition of language skills. While the primary aim of language instruction is enhanced proficiency in a language, we need to inculcate values-moral, spiritual, human, ethical, etc. in our teaching and learning activities. The paper demonstrates how this may be done while acquiring various language skills simultaneously. Such value-based education may be a contributing factor towards global peace.